2015
DOI: 10.1080/10438599.2015.1004245
|View full text |Cite
|
Sign up to set email alerts
|

The strategies of patent introduction into patent pools

Abstract: This article explores patterns of patent introduction into seven patent pools over time, analyzing 1337 essential patents. Pools grow significantly after their launch, in particular through the addition of new patents by incumbent members. The generality, width and significance of patents introduced into pools decreases significantly over time. Incumbent members file and introduce patents that are narrower, more incremental and less cited than new entrants. Pool members, however, also introduce patents relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…In both industries, they …nd that patent pools inhibit, rather than enhance, innovation by participating …rms. 3 In particular, Lampe and Moser (2010, forthcoming) show that the pool has discouraged patenting and innovation and attribute the negative incentive e¤ects of patent pools to the fact that patent pools create more formidable entities in court and thus increases the threat of litigation for outside …rms. Lampe and Moser (2013) further extend their empirical analysis to examine patent pools in 20 industries in the 1930s.…”
Section: Introductionmentioning
confidence: 99%
“…In both industries, they …nd that patent pools inhibit, rather than enhance, innovation by participating …rms. 3 In particular, Lampe and Moser (2010, forthcoming) show that the pool has discouraged patenting and innovation and attribute the negative incentive e¤ects of patent pools to the fact that patent pools create more formidable entities in court and thus increases the threat of litigation for outside …rms. Lampe and Moser (2013) further extend their empirical analysis to examine patent pools in 20 industries in the 1930s.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding patent pools, our paper introduces an organizational perspective on patent pools that complements previous studies in three ways (Joshi and Nerkar, ; Layne‐Farrar and Lerner, ; de Uijl et al ., ; Baron and Delcamp, ). First, our conceptual framework highlights organizational capacities to manage both licensing‐in and licensing‐out and to balance the tradeoff between value creation and value capture in patent pools.…”
Section: Discussionmentioning
confidence: 99%
“…Third, our findings explain patent pool outcomes by revealing the underlying process of patent integration. Baron and Delcamp () found that after their formation, patent pools grow significantly as incumbent members continue to add new patents. We provide a firm‐level explanation for this phenomenon by showing when (evolution of standard specifications) and how (adjust, divide and extend) a company continues to integrate more patents into pools.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations